Cerebral Abscess Caused by Listeria monocytogenes: Case Report and Literature Review - Cipriani, Debora; Trippel, Michael; Buttler, Klaus Jürgen; Rohr, Eva; Wagner, Dirk; Beck, Jürgen; Schnell, Oliver (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Listeria monocytogenes is an opportunistic gram-positive, facultative intracellular bacterium that causes invasive diseases mostly in pregnant women and immunosuppressed patients. Despite the predilection toward the central nervous system (CNS), it usually causes meningitis and meningoencephalitis, whereas brain abscesses are very uncommon. Case presentation We describe the case of a 69-year-old homeless patient with a brain abscess due to L. monocytogenes who was successfully treated surgically by a guided stereotactic aspiration and antibiotic therapy with ampicillin and gentamicin. Our patient was discharged after 4 weeks of therapy without neurologic deficits. Additionally, we provide a review of the literature of brain abscesses caused by L. monocytogenes. Conclusions This case highlights the need to drain cerebral abscesses and culture pus to correctly treat patients with antibiotics, especially given the high mortality rate of this infectious entity.
CRIS-Team Scopus Importer:2023-09-13
Keywords: brain abscess; immunocompromised; Listeria monocytogenes; meningitis